Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Karyawan PT Insani Medical Centre Jakarta - Maulidia, Rahma; Dja'far, Abu Bakar (Journal of Research and Publication Innovation, 2024)
By doing this research, it will be found how the influence of Organizational Culture and Work Motivation on Employee performance. Therefore, the need for this research by looking at the hypothesis of how positive and significant the influence between Organizational Culture and Work Motivation on Employee performance. The research method uses quantitative methods with a descriptive approach. The research site was conducted at PT Insani Medical Center Jakarta and the research time was 6 months. The results showed that organizational culture and motivation were in the same strong category. In the Hypothesis test in this study Ho was rejected and Ha was accepted, meaning that Organizational Culture and Work Motivation have a significant effect on employee performance at PT Insani Medical Center Jakarta, and have an influence of 45.2% on Employee Performance. While the remaining 58.8% is influenced by other factors